682 Efficacy and Safety of Balneotherapy using Diverse Natural Resources in Lithuania: A Multicenter Study (Balneo and PRM Research Journal, 2024)
Background: Balneotherapy or spa therapy, with its multimodal effects, has shown clinical efficacy in treating various pathological conditions. However, further studies are needed to assess its impact on mental health and to evaluate treatment safety. This study aimed to evaluate the effectiveness of different natural resources of the Lithuanian medical spa for stress-related disorders and skin health and to disclose the safety profile of using natural resources. Methodology. We performed a multicenter randomized controlled single-blinded study in 6 Lithuanian medical spas. The 1- 2-week treatment combining mineral water, therapeutic mud, and salt procedures was provided for the 364 participants with moderate stress levels and the effect was evaluated using surveys, instrumental, and laboratory measures. Results. The findings highlighted that the effects of BT using different natural resources significantly improve mental and skin health, as well as contribute to overall health status for up to 6 months. A significant reduction of anxiety, depression, and fatigue as well as improvement in sleep, skin moisture, subjective skin state, and integrative outcomes was achieved in all centers after treatment, while stress and saliva cortisol, working speed, skin oiliness, and elasticity improved in a few centers. A positive result was related to the duration of the treatment, and possibly- to the features of natural resources. Mineral water most commonly caused side effects; it varied among centers, however, they were predominantly local, mild, and transient. Conclusions. Balneotherapy using natural resources is effective for the enhancement of mental and skin health. Further research is necessary for a better understanding of the role of different natural resources on health status and safety profile.